2020
DOI: 10.37256/ser.122020422
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and E-Learning: the Challenges of Students in Tertiary Institutions

Abstract: Problems associated with the transition from conventional learning (face to face) to online learning (e-learning) in the educational system are well documented. The present study explores the challenges students in tertiary institutions have reported facing in online learning in the era of coronavirus pandemic. Using a sample (n = 141), an initial principal component factor analysis was conducted to group the constructs. Eight groups that emerged were social issues, lecturer issues, accessibility issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
174
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(196 citation statements)
references
References 8 publications
11
174
0
11
Order By: Relevance
“…The students believed that the internet data is expensive, limitation on internet access and devices lead to difficulties for them to participate in online learning. This is in line with previous studies conducted by Adedoyin and Soykan (2020), Hawati and Jarud (2020) and Aboagye et al (2020). Internet and devices are important for students and academicians during online learning.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The students believed that the internet data is expensive, limitation on internet access and devices lead to difficulties for them to participate in online learning. This is in line with previous studies conducted by Adedoyin and Soykan (2020), Hawati and Jarud (2020) and Aboagye et al (2020). Internet and devices are important for students and academicians during online learning.…”
Section: Discussionsupporting
confidence: 93%
“…Most of the students preferred face-to-face learning compared to the online learning. Aboagye, Yawson and Appiah (2020) also supported that the students were not ready to adapt and lack of motivation during online learning. A study conducted in Malaysia by Allam, Hassan, Mohideen, Ramlan and Kamal (2020) confirmed that the students lack of motivation during online learning.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations